Complex biogeographical patterns support an ecological connectivity network of a large marine predator in the north‐east Atlantic. Issue 2 (11th December 2018) - Alves, Filipe; Alessandrini, Anita; Servidio, Antonella; Mendonça, Ana Sofia; Hartman, Karin L.; Prieto, Rui; Berrow, Simon; Magalhães, Sara; Steiner, Lisa; Santos, Rui; Ferreira, Rita; Pérez, Jacobo Marrero; et al.
Abstract: Aim: The knowledge of a species biogeographical patterns greatly enhances our understanding of geographical ecology, which can improve identifying key conservation needs. Yet, this knowledge is still scarce for many marine top predators. Here, we aim to analyse movement patterns and spatial structuring of a large predator, the short‐finned pilot whale Globicephala macrorhynchus, over a wide geographical area. Location: North‐east Atlantic, in Macaronesian archipelagos (Azores, Madeira and Canaries) and Iberian Peninsula (Sagres). Methods: We used likelihood techniques to estimate residency times and transition probabilities and carried out social analysis from individual photographic identification data, and analysed year‐round distribution from effort‐related sightings, collated between 1999 and 2015. Results: The best‐fitting models included emigration and reimmigration and showed different residency times within each archipelago. A total of 26 individual movements from 21 individuals (from a sample of >2, 300 individuals) were recorded between Madeira and the neighbouring archipelagos, and heterogeneous transition probabilities were estimated within and between areas. A social network diagram showed associations from animals with distinct residency patterns. Higher significant sighting rates were recorded during autumn in the Azores and Madeira. Main conclusions: The variation in site fidelity and year‐round occupancy among areas of the Macaronesia is consistent with some degree of population structuring, which combined with a connectivity network and seasonal inflows from animals inhabiting offshore waters, support the development of a complex social and geographical ecology in short‐finned pilot whales. The combination of techniques applied in this study was an effective way to estimate parameters of movement, which could be a good practice to be used for other scenarios and species.